Eosinophil count and tumor necrosis factor α in response to phototherapy treatment of neonatal hyperbilirubinemia: a cross sectional study - Mai Rabie El-Sheikh; Amira Youssef Ahmed; Abd EL-Rahman Mohamed ELMashad; Ibrahim Ibrahim Talaye; Eslam El-Sa (BMC, 2022)
Abstract Background Phototherapy (PT) is the most often utilized technique for treating and preventing severe hyperbilirubinemia in the term and preterm newborns. PT's proven benefit is that it decreases the requirement for exchange transfusions. To investigate the effect of PT on allergic response mediators in neonates with hyperbilirubinemia treated by PT, eosinophil counts and tumor necrosis factor alfa levels have been assessed. Methods This cross-sectional study included 100 full-term infants with indirect hyperbilirubinemia in the first two weeks of life who were indicated for PT. They were investigated by tumor necrosis factor α and eosinophil counts before and 72 h after starting PT. The used tests were paired with Student's t-test and Pearson coefficient. Results Relative and absolute eosinophil counts and tumor necrosis factor alfa were significantly higher after PT than before (p < 0.001). There was a significant positive correlation between total serum bilirubin and both tumor necrosis factor alfa and eosinophil % (r = 0.442 and r = 0.362, respectively, P < 0.001) before PT. There was a significant positive correlation between total serum bilirubin and both eosinophil count and eosinophil % (r = 0.281and r = 0.339), respectively (P < 0.001) after PT. There was a significant positive correlation between both tumor necrosis factor alfa and eosinophil % after PT (r = 0.545, P < 0.001). Conclusions Serum tumor necrosis factor-alpha and eosinophilic count increased after treatment of neonatal hyperbilirubinemia by PT, which indicates an allergic response to PT in neonates.